2019
DOI: 10.3390/metabo9090177
|View full text |Cite
|
Sign up to set email alerts
|

Oxylipin Profiling of Alzheimer’s Disease in Nondiabetic and Type 2 Diabetic Elderly

Abstract: Oxygenated lipids, called “oxylipins,” serve a variety of important signaling roles within the cell. Oxylipins have been linked to inflammation and vascular function, and blood patterns have been shown to differ in type 2 diabetes (T2D). Because these factors (inflammation, vascular function, diabetes) are also associated with Alzheimer’s disease (AD) risk, we set out to characterize the serum oxylipin profile in elderly and AD subjects to understand if there are shared patterns between AD and T2D. We obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…An interesting finding of our work is an increase of OEA and EPA, substances that are known preventers of oxidative stress [33,34]. Although oxidative stress can be viewed as a common disruption in various pathologies, which may suggest similarities in the oxidized forms of lipids, the variations in the oxylipin profiles obtained in various diseases do not support this point of view [24][25][26]28,29]. Our data sheds light onto some appropriate compensatory mechanisms that may be involved in WD.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…An interesting finding of our work is an increase of OEA and EPA, substances that are known preventers of oxidative stress [33,34]. Although oxidative stress can be viewed as a common disruption in various pathologies, which may suggest similarities in the oxidized forms of lipids, the variations in the oxylipin profiles obtained in various diseases do not support this point of view [24][25][26]28,29]. Our data sheds light onto some appropriate compensatory mechanisms that may be involved in WD.…”
Section: Discussionmentioning
confidence: 85%
“…Oxylipin profiles were investigated for the study of mechanisms, and as diagnostic markers for diseases, such as Alzheimer's disease [24], female breast cancer [26], alcohol-related liver disease [25], atherosclerotic diseases [28], and coronary artery disease [29]. Importantly, every disease was characterized by a special set of oxylipins: 9-HODE [26], 20-HETE [25], 8-HETE, LTB4, 9-HODE and 13-HODE [28], 9-HETE, and F(2)-isoprostanes [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though there is a controversy, in randomized clinical trials studying the effects of ω-3 PUFAs in AD, most observational studies have shown the beneficial effects of ω-3 intake on reducing the incidence of AD [ 9 , 13 , 18 ]. Additionally, the oxylipin profiles of blood serum in AD subjects show around 20% higher levels of dihydroxyeicosatrienoic acid (which is the product of the sEH metabolism of the epoxy-metabolite of AA) as compared to the elderly individuals that were cognitively healthy [ 20 ]. Therefore, sEH is an important enzyme in PUFA metabolism and a lucrative drug target for NDs [ 21 ].…”
Section: Introductionmentioning
confidence: 99%